P075 Inflammation-induced cancer vs. cancer-induced inflammation is dependent on S1P lyase. (16th January 2018) - Schwiebs, A; Herrero San Juan, M; Wiercinska, E; Anlauf, M; Ottenlinger, F; Schmidt, K; Thomas, D; Elwakeel, E; Weigert, A; Bönig, H; Scholich, K; Geisslinger, G; et al.
Abstract: Background: The dichotomy of inflammation-induced cancer vs. cancer-induced inflammation is still enigmatic. Since sphingolipids are involved in both tumour cell survival and immune cell differentiation, migration and cytokine pattern we hypothesised their essential role in both mechanism of cancer development. Methods: We employed inducible S1P lyase (SGPL1) knockdown bone marrow-chimeric mice in a colitis associated colon cancer model leading to compartment-specific accumulation of sphingolipid levels. Results: We found that, independent of the compartment of SGPL1 deficiency, haematopoietic or extra-haematopoietic, DSS/AOM-treated mice demonstrated tumours with s1pr1, stat3, and IL-6 elevation. However, compartment-specific actions of the SGPL1-S1P axis contributed both morphologically and genetically to a very distinct development of inflammation and carcinogenesis. Haematopoietic SGPL1 knockdown forced severe inflammatory colitis with delayed carcinogenesis characterised by pdcd4-down-regulation. In contrast, extra-haematopoietic SGPL1 knockdown triggered a much more rapid occurrence of epithelial-driven sphingosine kinase 1-positive tumours, exhibiting kras, egfr and IL23-p19 signatures and a weak but distinct Th2 driven immune microenvironment. Moreover, we found that SGPL1 derived from haematopoietic cells is sufficient for S1P-driven lymphocyte sequestration. Conclusions: In this study we demonstrate that compartment-specific sphingolipid modulation clarifies the dichotomy of inflammation-induced cancer vs. cancer-induced inflammation.